Using Rapid and ELISA Test for Detection Hepatitis C Virus and Human Immunodeficiency Virus among Healthy and Renal Failure Population - Huda J.B. Al-Khilkhali (Journal of Global Pharma Technology, 2019)
Human immunodeficiency virus (HIV)-infected, hepatitis c virus (hcv)-uninfected sufferers are at risk for incident hcv infection, however little is understood approximately screening practices for incident hcv among HIVinfected individuals in HIV primary care clinics. The current study aimed at detecting the prevalence of HCV and human immunodeficiency virus (HIV) infection among haemodialysis patients that suffering from chronic kidney disease and healthy people using the Rapid Immunochromatographic Test (ICT) and enzyme linked immunosorbent assay (ELISA) In In the detection of these viruses .This study was carried out during the period from the November (2017) to January (2018), , a total of (28) patient on HD was collected from Specialized Center for Diseases and Kidney Transplant in AL-Sadder Medical City in AL- Najaf Governorate, and(30) samples Represented healthy people collected from the University of Kufa Faculty of Science.All samples ranged in age (20- 45) years. There were 35 male and 23 female. Viral detection revealed that there were 11(19%) was positive and 47(81%) was negative in Rapid (ICT). We further tested samples with ELISA for confirmed results Similarly 58 samples were tested for HCV out of which 16(28%) were ELISA positive and 42(72%) were negative for anti- HCV antibody but the age group(20- 28)year revealed high significant(p<0.05) in the ratio of infection with hepatitis C virus 71% (5:7)  than other age groups. the results of this study showed  high sensitivity and specificity for rapid (ICT) in present study represent good result for depend rapid test for detection of hcv antibodies and  first-line tests in screening and prognosis of hcv infection..in all groups of patient's seropositive anti-HCV antibodies and seronegative anti-HCV tested for anti-HIV Ab typ1 and typ2 by Rapid (ICT) were negative (0.00%) in all age groups in both sexes. The current study showed that males are more affected with HCV (56%) than females (44%) and the prevalence of hcv contamination amongst kidney failure patients in this study was 57%. Results of the current study showed that the healthy groups were negative anti-HCV Ab by both methods.Keywords: Hepatitis C virus, Chronic kidney disease, Hemodialysis patients, ELISA, Rapid (ICT).